DLTS study of extended defects in HgCdTe photodiodes. (May 2019) - Guinedor, P; Broult, T; Brunner, A; Rubaldo, L; Bauza, D; Reimbold, G; Kerlain, A; Destefanis, V
Abstract: Extended electrically active defects have been investigated in Short Wave InfraRed (SWIR) HgCdTe n on p photodiodes, using the Deep Level Transient Spectroscopy (DLTS) technique. Three localized defects have been found in the dislocations core or in their close environment. DLTS studies have also been performed before and after indentation, a technique which generates dislocations in the material. DLTS spectra are discussed and dislocations generated by indentation have been found to be electrically active only after annealing.